Evaluating present-day and future impacts of agricultural ammonia emissions on atmospheric chemistry and climate - M. Beaudor; M. Beaudor; D. Hauglustaine; J. Lathière; M. Van Damme; M. Van Damme; L. Clarisse; N. Vuichard (Atmospheric Chemistry and Physics)
Agricultural practices are a major source of ammonia (NH3) in the atmosphere, which has implications for air quality, climate, and ecosystems. Due to the rising demand for food and feed production, ammonia emissions are expected to increase significantly by 2100 and would therefore impact atmospheric composition such as nitrate (<msubsup>NO3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="4c315b3ea451cf26923ad12993612b33"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2017-2025-ie00001.svg" width="25pt" height="16pt" src="acp-25-2017-2025-ie00001.png"/></svg:svg>) or sulfate (<msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="6060a0eb6022af681aa55d19b3180df9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2017-2025-ie00002.svg" width="29pt" height="17pt" src="acp-25-2017-2025-ie00002.png"/></svg:svg>) particles and affect biodiversity from enhanced deposition. Chemistry–climate models which integrate the key atmospheric physicochemical processes with the ammonia cycle represent a useful tool to investigate present-day and also future reduced nitrogen pathways and their impact on the global scale. Ammonia sources are, however, challenging to quantify because of their dependencies on environmental variables and agricultural practices and represent a crucial input for chemistry–climate models. In this study, we use the chemistry–climate model LMDZ–INCA (Laboratoire de Météorologie Dynamique–INteraction with Chemistry and Aerosols) with agricultural and natural soil ammonia emissions from a global land surface model ORCHIDEE (ORganising Carbon and Hydrology In Dynamic Ecosystems), together with the integrated module CAMEO (Calculation of AMmonia Emissions in ORCHIDEE), for the present-day and 2090–2100 period under two divergent Shared Socioeconomic Pathways (SSP5-8.5 and SSP4-3.4). Future agricultural emissions under the most increased level (SSP4-3.4) have been further exploited to evaluate the impact of enhanced ammonia emissions combined with future contrasting aerosol precursor emissions (SSP1-2.6 – low emissions; SSP3-7.0 – regionally contrasted emissions). We demonstrate that the CAMEO emission set enhances the spatial and temporal variability in the atmospheric ammonia in regions such as Africa, Latin America, and the US in comparison to the static reference inventory (Community Emissions Data System; CEDS) when assessed against satellite and surface network observations. The CAMEO simulation indicates higher ammonia emissions in Africa relative to other studies, which is corroborated by increased current levels of reduced nitrogen deposition (NHx), a finding that aligns with observations in west Africa. Future CAMEO emissions lead to an overall increase in the global NH3 burden ranging from 59 % to 235 %, while the <msubsup>NO3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="8a872e45f44a0fc3c08e466e371cfb3a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2017-2025-ie00003.svg" width="25pt" height="16pt" src="acp-25-2017-2025-ie00003.png"/></svg:svg> burden increases by 57 %–114 %, depending on the scenario, even when global NOx emissions decrease. When considering the most divergent scenarios (SSP5-8.5 and SSP4-3.4) for agricultural ammonia emissions, the direct radiative forcing resulting from secondary inorganic aerosol changes ranges from −114 to −160 mW m−2. By combining a high level of NH3 emissions with decreased or contrasted future sulfate and nitrate emissions, the nitrate radiative effect can either overcompensate (net total sulfate and nitrate effect of −200 mW m−2) or be offset by the sulfate effect (net total sulfate and nitrate effect of +180<mspace linebreak="nobreak" width="0.125em"/>mW<mspace linebreak="nobreak" width="0.125em"/>m-2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="69pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="8077a7ec204171760d118275ba53fc24"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2017-2025-ie00004.svg" width="69pt" height="13pt" src="acp-25-2017-2025-ie00004.png"/></svg:svg>). We also show that future oxidation of NH3 could lead to an increase in N2O atmospheric sources from 0.43 to 2.10 Tg N2O yr−1 compared to the present-day levels, representing 18 % of the future N2O anthropogenic emissions. Our results suggest that accounting for nitrate aerosol precursor emission levels but also for the ammonia oxidation pathway in future studies is particularly important to understand how ammonia will affect climate, air quality, and nitrogen deposition.